Deliberate self-poisoning in a tertiary pediatric hospital - Vitória Cadete; Ema Freitas; Inês Fontes; Manuel Almeida; Fátima Rato; António Marques; Sandra Pires; Rita Machado (Publicaciones Permanyer, 2024)
Introduction and objectives: Deliberate self-poisoning (DSP) is a frequent cause of admission at the emergency department during adolescence. Since the beginning of the COVID-19 pandemic, a higher number of cases was reported. This retrospective study aimed to determine DSP prevalence, between 2018 and 2022, as well as the medication used and the method for obtaining it, within the catchment area of a Tertiary Pediatric Hospital Emergency Department (ED) in Portugal. Methods: Retrospective study, including patients aged 10 to 17 that lived in the catchment area of the ED and were admitted for DSP less than 7 days prior. By searching with the keywords "DSP" and "deliberate self-poisoning", 2975 records were found, of which 1403 cases were included. Statistical analysis was performed in SPSS with a significance level of 0.01. Results: Out of 1403 cases, 87.9% were female, mostly in mid-adolescence and with a previous follow-up appointment with a child and adolescent psychiatrist. The patient's own psychotropic medication were the most used drugs. Episodes with no suicidal intention were more frequent. After the ED, most cases were discharged with a referral for psychiatric follow-up. There was a higher number of DSP in 2021 (p < 0.01), with a prevalence of 123.8/100,000. Discussion: DSP is growing among adolescents. Cases increased significantly in 2021. We highlight the need for prevention campaigns and vigilance systems to monitor and modify this trend.